СРАВНИТЕЛЬНЫЙ АНАЛИЗ СЕМАНТИЧЕСКИХ КЛАССОВ ПЕРЕХОДНЫХ ГЛАГОЛОВ, УПРАВЛЯЮЩИХ ФОРМОЙ ДАТЕЛЬНОГО ПАДЕЖА И ИХ СООТВЕТСТВИЯ В УЗБЕКСКОМ ЯЗЫКЕ - Абдурахманов, Ф.И.; Дильманов, И.О. (SCIENCE and SOCIETY, 2018)
The article is devoted to the description of the semantic representations that can be derived from the interpretation of actantial verb structures that are called frames by Fillmore. In the article it is assumed that in the semantic interpretation of distributive-transformational scheme the communique between frames of minimal interpretation of case determines the case meaning of each of the actants.
Keywords: the frame; the value of case; actant; semantic class; nuclear structure; transforms; actantial verb; distribution of an element